Motivated Cue Integration in Alexithymia: Improving Interoception and Emotion Information Processing by Awareness-of-Sensation Techniques - Shalev, Idit (Frontiers in Psychiatry, 2019)
Recent findings indicate that alexithymia is the result of a multidomain, multidimensional failure of interoception (Murphy et al., 2018). Whereas much of the literature addresses the cognitive and affective aspects of alexithymia, less is known about the association between the failure of interoception and the process of motivated cue-integration. The theory of motivated cue integration (Shalev, 2015, 2018) integrates high level control processes with low level embodied and contextual cues, suggesting that selective attention to internal and contextual cues results in the creation of meaning that, in turn, influence judgement and action generation. Conceptualized as a special case of the cue integration problem, alexithymia may be associated with restricted access to emotional cues, indicating impaired connectivity between low-level embodied cues and top-down goals and values. This problem may also viewed as a means substitution problem (Kruglanski et al, 2002), indicating the individual’s need for alternative multisensory information. Based on this reasoning, interventions that exploit awareness of sensation techniques (e.g., mindfulness, experiential approach, focusing) may help to improve the distinction between bodily sensation and interpretation and to create meaning of situational state by substitution of inaccessible affective cues with alternative cues. Accordingly, clinicians and neuropsychologists can help individuals who suffer from alexithymia by training them to use awareness of sensation techniques and directing their attention to alternative multisensory cues as well as alternative cognitive configurations. Integrating peripheral cues in the moment-by-moment generation of meaning and self-regulation can improve affective judgement through the exchange of inaccessible affective cues with alternative ones.